The Influence of Tam and Security Factors on Interest in Using KAI Access For Generation X in Pasuruan - Yaqin, Ainul; Akramiah, Nurul; Subagio, Dyajeng Puteri Woro (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study was to evaluate how Generation X in Pasuruan City felt about the Access By KAI application in terms of perceived security, usefulness, and convenience of use. With 96 samples, a multiple linear regression analysis was performed. A significant value below the threshold supported the conclusions that interest in use is influenced by perceived security, utility, and convenience of use taken together. Only perceived ease of use, on the other hand, showed a significant effect on interest in usage when looked at separately. On the other hand, perceived security's significance value also exceeded the threshold, with a calculated t value above the t table, suggesting it does not significantly affect interest in use, while perceived usefulness's significance value exceeded the threshold, with a calculated t value lower than the t table.